Quantification of green-blue ratios, impervious surface area and pace of urbanisation for sustainable management of urban lake-land zones in India: A case study from Bengaluru city - Harini Santhanam; Rudrodip Majumdar (Journal of Urban Management, 2022)
Quantification of the ecosystem services of blue and green infrastructure in urban centres with the perspective of planning sustainable development is usually data-intensive, includes use of multi-platform datasets and adds to the complexities in deriving effective and reproducible metrics. The present study describes the creation of four simple metrics to estimate: 1. the ratio of 'green' vegetated areas to the 'blue' water spread areas, defined as the "Green-blue ratio" (GBA); 2. The ratio of 'blue' water spread areas to "built-up" ratio around the lakes, defined as the 'Blue to Built-up ratio' (BBA), 3. the percentage of impervious surface area (ISA) and 4. the pace of urbanisation in the dynamic zones (DZ) of urban lake environments. These new metrics were evaluated using landcover areas mapped from satellite imageries. Visual interpretation-based method was adopted to delineate the green, blue and built-up areas from Google Earth, which is suitable for wide range of users. The use of these metrics has been illustrated using available datasets for four representative lakes in Bengaluru city, India: Sankey tank, Ulsoor lake, Nagavarakere and Puttenahallikere. Significant spatio-temporal variations in the ratios of GBA and BBA as well as %ISA were observed and satisfactorily reflected the ecological status of these lakes in concurrence with earlier studies. Detailed analyses constrained a permissible rate of annual increase in the built-up area within the DZs to ∼ 3% for sustainable development of the lakes. The present set of metrics can be recommended as useful tools for urban planners and citizen scientists for seasonal monitoring of urban lake environments.
Keywords: 710; Blue-built up area ratio; Green-blue ratio; Green-built up area ratio; Impervious surface area; Urban lakes; Urban sustainability